PENGARUH INOVASI PRODUK, KINERJA PEMASARAN DAN ORIENTASI PASAR TERHADAP KEUNGGULAN BERSAING (STUDI PADA TOKO ROTI DI KABUPATEN GRESIK) - Anik Rachmatullina’iya (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
This research to analyze the influence of product innovation, performance marketing and market orientation towards competitive advantage bakery in Gresik Town. This study uses the analysis of multiple linear regression, with incidental sampling technique. In this study using quantitative methods with 50 samples of existing bakery in Gresik Town. Processing of the data from this study using SPSS version 15. The results of the study showed that the t test, t count > t table is 2,096 > 2,0219, then the Product Innovation positive effect on competitive advantage t count < t table is 1,293 < 2,0219, This shows that marketing performance is not a positive influence on competitive advantage. t count > t table is 5,900 > 2,0219, the market orientation has positive influence on competitive advantage. The results of the study showed that the test F, 82,665 F count > F table 2.81 and significance F value smaller than 0.05 (0.000 < 0.05 ), then product innovation, performance marketing and market orientation simultaneously affect the competitive advantage.